Optical Fiber as a Basis for Creation Light Sensor - A. O. Zenevich; S. V. Zhdanovich; T. A. Matkovskaia; E. V. Novikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The possibility of using telecommunication optical fiber as a basis for creating a light sensor is shown. The light sensor is a section of optical fiber wound on a cylindrical base turn to turn. A photodetector is connected to the output end of this fiber section. When comparing the possibility of using single-mode and multimode telecommunication optical fiber in the sensor, it is noted that multimode optical fiber is most suitable for creating such a sensor. It is established that the sensitivity of the sensor to the luminous flux increases with a decrease in the bending radius of the optical fiber and with an increase in the number of turns of the sensor. Dependences of the sensitivity of the sensor to the luminous flux on the number of turns and their diameter are obtained, which allow developing specific design solutions for such sensors.